1999
DOI: 10.2307/176661
|View full text |Cite
|
Sign up to set email alerts
|

Responses in Microbes and Plants to Changed Temperature, Nutrient, and Light Regimes in the Arctic

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology. Abstract. Previous research has shown that experimental perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
134
4
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(152 citation statements)
references
References 23 publications
11
134
4
2
Order By: Relevance
“…In addition, we measured treatment effects on above-and belowground components of plant biomass/nutrient content. This study differs from previous studies on the effects of warming on C balance in mesic/moist tundra (Chapin et al 1995;Christensen et al 1997;Hobbie and Chapin 1998;Jones et al 1998;Jonasson et al 1999) in several major ways. First, it is a short-term study requiring a destructive harvest to determine the initial warming responses not just of GEP and ER, but also of respiration from belowground.…”
Section: Introductioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In addition, we measured treatment effects on above-and belowground components of plant biomass/nutrient content. This study differs from previous studies on the effects of warming on C balance in mesic/moist tundra (Chapin et al 1995;Christensen et al 1997;Hobbie and Chapin 1998;Jones et al 1998;Jonasson et al 1999) in several major ways. First, it is a short-term study requiring a destructive harvest to determine the initial warming responses not just of GEP and ER, but also of respiration from belowground.…”
Section: Introductioncontrasting
confidence: 74%
“…Soil temperatures are generally warmer in tussock than inter-tussock areas (Table 1; Chapin et al 1979). Long-term warming and fertilisation studies indicate that tundra ecosystems are more responsive to increased nutrient availability than to warmer temperatures (Chapin et al 1995;Jonasson et al 1999). Consequently, the strong nutrient limitation at our site (Chapin et al 1995) suggests that the enhanced tussock leaf nutrient pools (Table 3) and vascular plant primary production in manipulated tussocks resulted from higher soil nutrient availability associated with warming of tussock soils.…”
Section: Effects Of the Manipulationmentioning
confidence: 84%
“…Indeed, nitrogen is commonly suggested to be the more important limiting factor in arctic ecosystems (Chapin et al 2002;Jonasson et al 1999;Richardson et al 2002). In our study, however, soil temperature was far more important than nutrient availability in determining the biomass of Alopecurus.…”
Section: Potential Mechanismscontrasting
confidence: 57%
“…Gross ecosystem production (GEP, always positive), defined as the rate of plant photosynthesis, is calculated as the difference between NEP and ER: GEP=NEPER. For both a and b, means shown below with the same letter are not statistically different at the P 0.05 level of significance range of tundra types (e.g., Henry et al 1986;Jonasson et al 1996Jonasson et al , 1999Press et al 1998;Robinson et al 1998). In a meta-analysis of these past studies, Dorfmann and Woodin (2002) showed that increased nutrient availability consistently caused the greatest changes in aboveground biomass in tundra vegetation, that increased air temperature frequently also increased biomass, and that minor reductions in PAR had little effect while major reductions in PAR caused significant reductions in aboveground biomass and plant growth.…”
Section: Generality Of Treatment Responsesmentioning
confidence: 99%